Integrasi Nilai-Nilai Tasawuf dalam Psikoterapi Islam untuk Penguatan Kesehatan Mental Siswa di Era Digital - Lailla Aprilia Khairunnisyah; Umi Nur Holifah (Al-Kindi, 2025)
This study aims to analyze the integration of Sufi values into Islamic psychotherapy as a strategy to strengthen students’ mental health in the digital era through a literature review approach. The digital era presents various psychological challenges, including anxiety, distraction, gadget dependence, and a decline in emotional regulation, thereby requiring a more comprehensive spiritual approach. Sufi values such as tazkiyatun nafs, muraqabah, muhasabah, patience, and dhikr hold significant potential in helping students develop inner peace and mental resilience. Through an extensive examination and analysis of classical and contemporary literature, this study identifies that Sufi-based Islamic psychotherapy offers a holistic healing mechanism by integrating cognitive, emotional, and spiritual dimensions. The findings indicate that the internalization of Sufi values can enhance self-awareness, impulse control, emotional stability, and the ability to face academic and social pressures proportionally. This integration is also relevant for implementation in educational settings through the habituation of dhikr, spiritual mentoring, and value-based counseling. Thus, this study emphasizes the importance of Sufism as a foundational model of Islamic psychotherapy that is adaptive to students’ mental health needs in the digital era